Radiate and Planar Multipolar Neurons of the Mouse Anteroventral Cochlear Nucleus: Intrinsic Excitability and Characterization of their Auditory Nerve Input - Xie, Ruili; Manis, Paul B. (Frontiers in Neural Circuits, 2017)
Radiate and planar neurons are the two major types of multipolar neurons in the ventral cochlear nucleus. Both cell types receive monosynaptic excitatory synaptic inputs from the auditory nerve, but have different responses to sound and project to different target regions and cells. Although the intrinsic physiology and synaptic inputs to planar neurons have been previously characterized, the radiate neurons are less common and have not been as well studied. We studied both types of multipolar neurons and characterized their properties including intrinsic excitability, synaptic dynamics of their auditory nerve inputs, as well as their neural firing properties to auditory nerve stimulation. Radiate neurons had a faster member time constant and higher threshold current to fire spikes than planar neurons, but the maximal firing rate is the same for both cell types upon large current injections. Compared to planar neurons, radiate neurons showed spontaneous postsynaptic currents with smaller size, and slower but variable kinetics. Auditory nerve stimulation progressively recruited synaptic inputs that were smaller and slower in radiate neurons, over a broader range of stimulus strength. Synaptic inputs to radiate neurons showed less depression than planar neurons during low rates of repetitive activity, but the synaptic depression at higher rates was similar between two cell types. However, due to the slow kinetics of the synaptic inputs, synaptic transmission in radiate neurons showed prominent temporal summation that contributed to greater synaptic depolarization and a higher firing rate for repetitive auditory nerve stimulation at high rates. Taken together, these results show that radiate multipolar neurons integrate a large number of weak synaptic inputs over a broad dynamic range, and have intrinsic and synaptic properties that are distinct from planar multipolar neurons. These properties enable radiate neurons to generate powerful inhibitory inputs to target neurons during high levels of afferent activity. Such robust inhibition is expected to dynamically modulate the excitability of many cell types in the cochlear nuclear complex.